Efektivitas Media Edukasi Dalam Meningkatkan Kepatuhan pengobatan pada penderita Diabetes Melitus - Revalina nurfirliana; Reisa Mardiana putri; Elba Nur Fadilah H; Neng Siti Nur Puadah Nurpuadah; Nunik Nurliani; Miftahul Falah (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Diabetes mellitus is a major health problem globally and in Indonesia. Patient adherence to diabetes mellitus treatment significantly impacts treatment success. However, poor medication adherence remains a problem that can increase the risk of complications. Health education through various media, such as booklets, leaflets, and other media, is effective in improving patient adherence to treatment. The research method used was a literature review, with data sources from Google Scholar and the Garuda portal. The searched articles were full-text articles filtered for the last five years, from 2021 to 2026. The results showed that educational media is effective in improving medication adherence in diabetes mellitus patients.